A Novel Egr-1-Agrin Pathway and Potential Implications for Regulation of Synaptic Physiology and Homeostasis at the Neuromuscular Junction - MacDonald, Ryen; Barbat-Artigas, Sebastien; Cho, Chulmin; Peng, Huashan; Shang, Jijun; Moustaine, Ayman; Carbonetto, Salvatore; Robitaille, Richard; Chalifour, Lorraine E.; Paudel, Hemant (Frontiers in Aging Neuroscience, 2017)
Synaptic transmission requires intricate coordination of the components involved in processing of incoming signals, formation and stabilization of synaptic machinery, neurotransmission, and in all related signaling pathways. Changes to any of these components cause synaptic imbalance and disruption of neuronal circuitry. Extensive studies at the neuromuscular junction (NMJ) have greatly aided in the current understanding of synapses and served to elucidate the underlying physiology as well as associated adaptive and homeostatic processes. The heparansulfate proteoglycan agrin is a vital component of the NMJ, mediating synaptic formation and maintenance in both brain and muscle, but very little is known about direct control of its expression. Here, we investigated the relationship between agrin and transcription factor early growth response-1 (Egr-1), as Egr-1 regulates the expression of many genes involved in synaptic homeostasis and plasticity. Using chromatin immunoprecipitation, cell culture with cell lines derived from brain and muscle, and animal models, we show that Egr-1 binds to the AGRN gene locus and suppresses its expression. When compared with wild type (WT), mice deficient in Egr-1 (Egr-1-/-) display a marked increase in AGRN mRNA and agrin full-length and cleavage fragment protein levels, including the 22 kDa, C-terminal fragment in brain and muscle tissue homogenate. Because agrin is a crucial component of the NMJ, we explored possible physiological implications of the Egr-1-agrin relationship. In the diaphragm, Egr-1-/- mice display increased NMJ motor endplate density, individual area, and area of innervation. In addition to increased density, soleus NMJs also display an increase in fragmented and faint endplates in Egr-1-/- versus WT mice. Moreover, the soleus NMJ electrophysiology of Egr-1-/- mice revealed increased quantal content and motor testing showed decreased movement and limb muscle strength compared with WT. This study provides evidence for the potential involvement of a novel Egr-1-agrin pathway in synaptic homeostatic and compensatory mechanisms at the NMJ. Synaptic homeostasis is greatly affected by the process of aging. These and other data suggest that changes in Egr-1 expression may directly or indirectly promote age-related pathologies.